Analysis of the Advanced Encryption Standard (AES) Method in Securing Web-Based Exam Questions - Hasugian, Abdul Halim; Darta, Ali; Amalia, Rizki (Cattleya Darmaya Fortuna, 2023)
Data protection is a critical issue in the world Information volume technology, Most important in web-based systems that store sensitive information such as exam question data. This research aims to analyze AES Advanced Encryption Standard method as a tool to improve the security of web-based exam question data. This research utilizing a qualitative benchmark while carrying out a review library to understand the concepts and principles of AES, and analyzing the implementation and integration of AES in web-based systems. This research will also involve experiments by implementing a web-based exam question data security system using the AES method. Tests will be conducted by measuring system performance in terms of speed, reliability, and efficiency. In addition, a penetration test will also be conducted to evaluate the system's resistance to potential attacks from unauthorized parties. This research Hopefully we can provide more detailed information about data management web-based Questioning exam by applying approach AES. This research can also provide recommendations for the application of the AES method in other data security scenarios and contribute to facing data security challenges in the future. Thus, This argument can make a constructive contribution to building construction of secure and reliable web-based systems in storing and managing sensitive data.